(Physico chemical constants of some Indonesian essential oils and their GLC Finger Prints on OV Silicone 101 as Liquid Phase) - Nurlydia, Dede; Dharma, Gasik; Moestafa, Achmad (Warta Industri Hasil Pertanian, 1993)
Essential oils are volatile derived from plants, therefore Glc method of analysis is most recommended.Each oil have differentcomponents and quantitatively can be used as a standard if the same procedure is followed.In case from the different sample different"finger print" was found,the sample might be suspected to had been adulterated. The physico chemical constant of the oils are also described in this paper, hence it can be used as a standard for most indonesian commercial oils.